5.0k views
3 votes
How do you solve this equation 27s-29=54s-83

2 Answers

0 votes

Answer:

2

Explanation:

27s — 29= 54s — 83

First, you collect like terms

27s — 54s = — 83 + 29

— 27s = — 54

Next, divide both side by the coefficient of s i.e — 27

s = —54/ —27

s = 2

User Danny Goodall
by
5.0k points
6 votes

Answer: 2

Explanation:

27s - 29 = 54s - 83

First of all, subtract 27s from both sides, we get;

27s - 27s - 29 = 54s - 27s - 83

Which gives; - 29 = 27s - 83

Now, add 83 to both sides and we get;

-29 + 83 = 27s - 83 + 83

Which gives; 54 = 27s

Now,we divide both sides by 27 to get; 54/27 = 27s/27

When we divide both sides, the left hand side becomes 2,while the right hand side is "s"; hence, we get s=2 as the answer.

User Banjer
by
5.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.